PEMANFAATAN SIMBOL DAN ELEMEN TRADISIONAL MEGA MENDUNG SEBAGAI IDENTITAS VISUAL PRODUK LOKAL INDONESIA: The Utilization of Mega Mendung Traditional Symbols and Elements as Visual Identity for Local Indonesian Products - Paramitha, Jessica; Chandra, Edy (Universitas Trisakti, 2024)
The Utilization of Mega Mendung Traditional Symbols and Elements as Visual Identity for Local Indonesian Products. This research explores the utilization of the Mega Mendung batik motif in the visual identity design of Indonesian local products and its impact on market appeal. Through a qualitative approach, the research analyzes how the integration of traditional elements in the packaging of culinary and souvenir products can enhance visual appeal and add value to the products. The results indicate that consumers respond positively to products featuring designs that incorporate traditional elements, as they are perceived as more authentic and culturally valuable. The challenges of integrating traditional and modern elements can be addressed through effective collaboration between designers, producers, and other stakeholders to ensure a design that is both harmonious and market-appropriate. This study emphasizes the importance of traditional elements in creating a strong visual identity and product differentiation, as well as the need for a collaborative approach to enhance the competitiveness of local products in the global marketplace.